The Manager And His Job Skills - McLennan, Kenneth (Academy of Management Journal, 1967)
The author surveys 520 managers above the first-line supervisor level and concludes that managerial skills are neither universal nor unique to individual jobs. Neither is there any empirical evidence of effective functional transferability of managers between jobs, organizations or industries.